Christopher Brumfit award 2015. (21st December 2016) - Unknown
Abstract : The Editor and Board of Language Teaching are pleased to announce that the winner of the 2015 Christopher Brumfit thesis award is DrArmin Berger . The thesis was selected by an external panel of judges based on its significance to the field of second language acquisition, second or foreign language learning and teaching, originality and creativity, and quality of presentation.